MEMBACA DAN MELENGKAPI PETA DASAR UNTUK MENINGKATKAN KEMAMPUAN SISWA DALAM MEMAHAMI MATERI GEOGRAFI REGIONAL - Syaiful Khafid (Jurnal Ilmu Pendidikan, 2016)
This article reports on a classroom action research project aimed at improving the quality of geography learning of class XII IPS.1 students of SMAN 1 Sidayu, East Java. The learning activities in the study were carried out through three cycles in which the students were exposed to more frequent map reading exercises, were asked to complete basic map on their worksheets, and were also required to present their works in front of the class. The teaching-learning core technique employed was reading and completing basic map. Along the implementation of the technique, greater number of students demonstrated their better understanding of the geographical condition of a certain country. The technique also enhanced the students' achievements and interest in reading and understanding the condition of regional geography. In short, reading and completing basic map is a good technique to improve students' competence to understand geographical condition.